PERANCANGAN SISTEM SMARTCARD SEBAGAI PENGAMAN PINTU MENGGUNAKAN RFID BERBASIS ARDUINO - Ferry Sudarto; Gustasari Gustasari; Arwan Arwan (Universitas Raharja, 2017)
Along with the development of science and technology so rapidly trigger the emergence of new technologies, one of which is RFID. RFID (Radio Frequency Identification) is a process of identifying the object or objects using radio transmission frequency. RFID is a new technology, and will continue to evolve in line with advances in integrated circuit technology, it can be ascertained that the RFID tag can be applied in various fields. RFID systems offer increased efficiency in controlling inventory control in the identification of objects. RFID can be used to store and receive data remotely using a device that RFID TAG (transponder). Many applications can utilize RFID systems, for example for indoor security systems, highways, libraries, class attendance, even as the identity of the student / students. Therefore, in this researchRaharja College presenting a Smartcard System Design using RFID as a device interface and ARDUINO UNO as a controller to be used as a door security system. With the presence of this system is expected to be a useful new innovation in Raharja College and can improve the shortcomings of existing systems and can provide maximum service to the whole personal raharja.